PERANCANGAN ANIMASI 2D BAHAYA STUNTING BAGI ANAK USIA 0-5 TAHUN DI KABUPATEN PATI - Muqoddas, Ali; Senoprabowo, Abi; Prabowo, Dwi Puji; Langit, Tifa Sekar; Nugraini, Siti Hadiati (Jurnal Informatika UPGRIS, 2024)
Stunting is a condition where a toddler is smaller or shorter than his age. The Covid-19 pandemic has resulted in stunting cases in Indonesia increasing, including in Pati Regency. Stunting cases that occur in Pati Regency are mostly caused by wrong parenting patterns which, if not immediately addressed, children will experience mental, psychomotor and intellectual disabilities, and can affect human resources in the area. The research method in this design is qualitative with a framing analysis method. This design applies basic pre-production, production and post-production media methods. The main message in this design is an appeal for mothers to choose the right parenting style through 2D animation media..